Maternidade atrás das grades: a separação entre mães e filhos na unidade materno infantil de Ananindeua - VASCONCELOS, Maria Clara Costa (2019)
The present paper seeks to explain how the Bangkok Rules apply to the process of separation of the mothers of their children born in prison, specifically the provisions of Rules 50 and 52 in the Center for Female Reeducation – CRF/Ananindeua. Using a feminist epistemology, the present work set out to bring the female figure to the center of her analysis, leading women who, for more than enough time, were kept on the margins - if not totally excluded - of scientific research. In view of the fact that the edition of the Bangkok Rules during the 65th Assembly of the United Nations represents an international commitment to the construction of humanized penitentiary policies in the care of women in prison, greater urgency is the obedience, by the Brazilian prison units, of the international parameters imposed by the Rules in relation to the mothers who had to separate from the children born in jail, as well as the conditions of coexistence between mothers and children after this separation. Thus, initially, the present work will give a brief analysis of the impacts brought about by the construction of gender stereotypes for women, demonstrating how they encouraged the formation of a supposed "prey woman" profile, and then contrasting it with the public female prisoners in Brazil, according to data taken from official sources. The paper then describes the main international and national provisions on the treatment of prisoners, focusing specifically on legislation dealing with women. Subsequently, the research presents interviews with the women in prison situation of the Maternal and Child Unit of the Center for Female Reeducation and the techniques that work there, in order to demonstrate how the process of separation of the mothers of their children in this unit has been exercised prison. Finally, it is concluded that the CRF has the necessary structure to guarantee humanized policies to the mothers in jail, but fails when it establishes only one year of mother-child coexistence, without a case-by-case evaluation to know whether or not the extension of the child's stay is recommended. In addition, adequate spaces were not observed to receive the visitation of the children after their departure from jail, nor the use of incentives/resources of the CRF for this to occur. As a solution, it is argued that the Public Power may dispense greater resources for the CRF, so that it can encourage visitation and mother-child coexistence after separation, as well as construct and maintain specific spaces for this purpose.